Profile of Transepidermal Water Loss (TEWL), Skin Hydration, and Skin Acidity (pH) in Indonesian Batik Workers - Prakoeswa, Cita Rosita Sigit; Damayanti, Damayanti; Anggraeni, Sylvia; Umborowati, Menul Ayu; Febriana, Sri Awalia; Oginawati, Katharina; Tanziha, Ikeu (Hindawi Limited, 2022)
Chemical substances used during batik processing may affect the physiological function of the batik worker's skin barrier. This study assessed the level of transepidermal water loss (TEWL), skin hydration, and skin acidity in 61 batik workers from the batik center in Paseseh village, Tanjung Bumi subdistrict, Madura Island, Indonesia. Forty-five batik workers involved in dry work including drawing patterns on the cloth with wax and sixteen batik workers involved in wet work including dyeing the cloth with a dye bath were included in this study. The mean TEWL level in the dry work section was 59.87 ± 11.94 g/m2/h on the palmar and 29.00 ± 13.09 g/m2/h on the dorsal side of the hand, while the mean TEWL in the wet work section were 47.39 ± 9.66 g/m2/h on the palmar and 37.07 ± 10.00 g/m2/h on the dorsal side of the hand. The mean skin hydration level in the dry work section was 49.80 ± 19.16 arbitrary units (a.u.) for the palmar side and 52.77 ± 16.21 a.u. for the dorsal side of the hand, while the mean levels of skin hydration in the wet work section were 47 ± 12.73 a.u. and 62.94 ± 10.09 a.u. for palmar and dorsal side, respectively. The mean levels of skin acidity in the dry work section were 5.45 ± 0.19 for the palmar side and 5.30 ± 0.20 for the dorsal side of the hand, while the wet work section had 5.30 ± 0.19 and 5.10 ± 0.19 for the palmar and dorsal side of the hand, respectively. The TEWL levels were found to be higher on the palmar side of the hand in both the dry work and wet work sections, which was consistent with the measurement of skin hydration levels that were lower on the palmar side of the hand. The mean skin pH levels for both work sections were considered within the normal range. © 2022 Cita Rosita Sigit Prakoeswa et al.